Leveraging Supply Chain Visibility to Strengthen Risk Management: Insights from Information Processing Theory - Liaqut Ali; Muhammad Zia Ul Haq (Journal of Accounting and Finance in Emerging Economies)
Purpose: This research examines the role of supply chain visibility in enhancing supply chain risk management amidst increasing global uncertainties. Drawing on Information Processing Theory, it investigates how visibility across suppliers, customers, and internal operations enables firms to effectively identify, assess, and mitigate risks within their supply chain networks.